The study of serum lipid profile in patients with cirrhosis of liver - Pandey, Tilchan; Resham Gautam; Shami Pokhrel (Asian Journal of Medical Sciences, 2023)
Background: Cirrhosis of liver is a chronic condition of hepatocellular failure due to different etiology which leads multiple complications and increases the morbidity and mortality. The aim of the study was to study the lipid profile in patients with cirrhosis and to assess if it relates to the severity of the cirrhosis. Hence, abnormal lipid profile may be the surrogate marker of the severity of cirrhosis of liver. Aims and Objectives: Study lipid profiles in cirrhotic patients and compare with healthy population and to relate severity of cirrhosis of liver with the finding of abnormal lipids. Materials and Methods: This study was a cross-sectional study conducted in the department of internal medicine over a period of 6 months. It was carried on 51 cirrhotic patients and 50 non-cirrhotic subjects who attended the outpatient and inpatient department. The cirrhosis of liver was established with history, examination, and investigations. Results: The mean total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very LDL (VLDL), respectively, of non-cirrhotic subjects was found to be higher than cirrhotic patients, respectively. All lipid profiles TC, TG, HDL, LDL, and VLDL value found to be (P<0.05) which were statically significant. Serum TC, TG, HDL, LD, and VLDL level decreased more in Child-Turcotte-Pough Criteria (CTP) Class C as compared to CTP Class B. The TC, HDL, and LDL belonged cases to the CTP class C and B showed (P<0.05) found statistical significance, which can be further correlated with the severity of cirrhosis. In the present study, the level of TG and VLDL was (P>0.05) found statistically non-significant. Conclusion: All the lipid parameters decrease in cirrhotic patients as compare to non-cirrhotic subjects and progressively lower the parameters as severity of liver disease increased.